CW operation of high‐power blue laser diodes with polished facets on semi‐polar (202¯1¯) GaN substrates. Issue 24 (11th November 2016) - Pourhashemi, A.; Farrell, R.M.; Cohen, D.A.; Becerra, D.L.; DenBaars, S.P.; Nakamura, S.
Abstract : Continuous wave (CW) operation of high‐power blue laser diodes (LDs) with polished facets on semi‐polar (202̅1̅) gallium nitride (GaN) substrates is demonstrated. Ridge waveguide LDs were fabricated using indium GaN waveguiding layers and GaN cladding layers. At a lasing wavelength of 452 nm, the peak two‐facet CW output power from an LD with uncoated facets was 1.71 W at a current of 3 A, corresponding to an optical power density of 32.04 MW/cm 2 on each facet. The dependence of output power on current did not change with repeated CW measurements, indicating that the polished facets did not degrade under high‐power CW operation. These results show that polished facets are a viable alternative to cleaved or etched facets for high‐power CW semi‐polar LDs.